Sex education: A pending subject - Manzano Pauta, Diana Elisabeth; Jerves Hermida, Elena Monserrath (Maskana, 2015)
Despite advances in knowledge of sex education, lack of studies on the perspective of teachers and the importance of their role in teaching this subject to their teenage students, triggered the research presented in this paper. The study focuses on the knowledge, practices and attitudes of teachers from high schools in the city of Cuenca about sexual education of their adolescent students. We adopted a quantitative approach, using a questionnaire-based survey for data collection. The study population consisted of a sample of 180 teachers from public and private schools. Results reveal that a percentage of teachers never received training on sexual education. This lack of training is reflected in the limited engagement of teachers in addressing sex education in their classrooms, the abstinence of which leads to sexual health misconceptions.